POTTERYSCAPING BRUCE ONOBRAKPEYA’S FEMININE PLASTOGRAPH - T. E., Akinde; O. B., Ayodele; O. O., Abokede; A. S., Eyinade (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is on Potteryscape1 as exemplified in selected Bruce Onobrakpeya’s feminine plastographs. Bruce, an artist cum nonagenarian from Urhobo extraction of Nigeria, born in the early 1930s and trained in the late 1950s through to early 1960s. He is, to say the least, an eclectic experimentalist, exponential arbiter and living legend. Bruce is noted for his incredible vigour for breaking new ground, significantly plastograph. He is arguably, the most celebrated and decorated Nigerian modernist artist with over sixty years practicing exposition. Much as scholarships were on his art; apparent however, is dearth of discourse on his feminine plastograph and their Potterscapingness2. As such, this study attempts Potteryscaping3 Onobrakpeya’s artistry, particularly his feminine plastographs. Theoretical and methodical approaches were adopted; sourcing literary and artistic samples from books and the web through the internet of things (IoT), which were corroborated with personal communication. A total of five (5) plastographic pieces were shortlisted and subjected to potteryscaping extrapolation. They are Emete Ayuvbi, Emete Igboro Rain and cry at Otorogba, Adumadan, and Emuobonuvie, executed between 1972 and 1976. Finding revealed Potteryscapingness of the pieces as exemplified in the body accessory elements like beads, ivory and brass. It further attest women resilience, tenacity, empathy and tranquility. The study consequently, advocates adoption and promotion of Potteryscape as a genre in Visual arts, significantly by artists, scholars and art lovers in line with article five (5) and nine (9) of the Sustainable Development Goals.